Keperawatan FAKTOR YANG MEMPENGARUHI PENDERITA TB PARU DROP OUT MINUM OBAT ANTI TUBERKULOSIS - Jansen Parlaungan M.Kes (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2021)
FACTORS AFFECTING LUNGER TB PATIENTS DROP OUT DRINKING ANTI TUBERCULOSIS DRUGS Jansen Parlaungan1, Yenni Huriani2, Oktovina Mobalen3, Panel Situmorang4 Lecturer at the Health Polytechnic of the Ministry of Health in Sorong, West Papua e-mail: Yansenparlaungan@yahoo.co.id ABSTRACT Introduction: Tuberculosis has a high risk of death in Indonesia, treatment will be effective if the patient is adherent to taking anti-tuberculosis (OAT) drugs. Objective: To determine the factors that influence pulmonary TB sufferers dropping out of taking anti-tuberculosis (OAT) drugs at the Polik Pojok Dots RSUD Sele be Solu, Sorong City. Methods: This type of research is a quantitative research with the development method used is cross sectional, namely an epidemiological study that measures several variables at once. The research design used was ex post facto. The sampling technique used was total sampling. The sample consisted of 26 pulmonary tuberculosis patients who dropped out at the Polik Pojok Dots RSUD Sele be Solu, Sorong City. Results: The study showed that there was a relationship between attitudes and drop out incidence of pulmonary tuberculosis patients at the Corner of Dots of RSUD Sele be Solu, Sorong City, the value of P value = 0.002 <from α value of 0.05. Conclusion: It can be used by RSUD Sele be Solu in Sorong City in order to increase the provision of information about treatment methods, because pulmonary TB treatment takes a long time, so if pulmonary TB sufferers do not understand this, it is very likely that they will stop the ongoing treatment. and not finished. Keywords: Attitude; Drop Out; Pulmonary TB; Anti-Tuberculosis Medicine (OAT).